Measurement of color flow in tt̄ events from pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Aoki, M.; et al. (American Physical Society (APS), 2011)
We present the first measurement of the color representation of the hadronically decaying W boson in tt̄ events, from 5.3fb-1 of integrated luminosity collected with the D0 experiment. A novel calorimeter-based vectorial variable, jet pull, is used, sensitive to the color-flow structure of the final state. We find that the fraction of uncolored W bosons is 0.56±0.42(stat+syst), in agreement with the standard model. © 2011 American Physical Society.